Analysis of the role of the low threshold currents IT and Ih in intrinsic delta oscillations of thalamocortical neurons - Amarillo Gomez, Yimy (2015)
Fil: Amarillo Gomez, Yimy. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina